Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T21:50:46+01:00
2(x²-6x+9)-(x-7)=14-2(1-x²)
2x²-12x+18-x+7=14-2+2x²
-12x+18-x+7=14-2
-13x=12-25
-13x=-13
x=1

3(y²-2y+1)-(y+4)-12=3(y²-16)
3y²-6y+3-y-4-12=3y²-48
-6y+3-y-4-12=-48
-7y=-48+13
-7y=-35
y=5

9y²-12y+4-4(y²+2y+1)=5(y²-1)-1
9y²-12y+4-4y²-8y-4=5y²-5-1
-12y+4-8y-4=-5-1
-20y=-6
y=6/20
y=3/10

2(z-0,5)=4z²-9-4(z²-6z+9)
2z-1=4z²-9-4z²+24z-36
2z-1=-9+24z-36
22z=44
z=2

3(z²-2z+1)-2(z²-4z+4)-12z=6-(1-z²)
3z²-6z+3-2z²+8z-8-12z=6-1+z²
-6z+3+8z-8-12z=6-1
-10z=5+5
10z=10
z=1



2009-12-07T23:18:32+01:00
B)
3(y²-2y+1)-(y+4)-12=3(y²-16)
3y²-6y+3-y-4-12=3y²-48
-6y+3-y-4-12=-48
-7y=-48+13
-7y=-35
y=5

a)
2(x²-6x+9)-(x-7)=14-2(1-x²)
2x²-12x+18-x+7=14-2+2x²
-12x+18-x+7=14-2
-13x=12-25
-13x=-13
x=1


c)
9y²-12y+4-4(y²+2y+1)=5(y²-1)-1
9y²-12y+4-4y²-8y-4=5y²-5-1
-12y+4-8y-4=-5-1
-20y=-6
y=6/20
y=3/10
e)
3(z²-2z+1)-2(z²-4z+4d-12z=6-(1-z²)
3z²-6z+3-2z²+8z-8-12z=6-1+z²
-6z+3+8z-8-12z=6-1
-10z=5+5
10z=10
z=1
c)
2(z-0,5)=4z²-9-4(z²-6z+9)
2z-1=4z²-9-4z²+24z-36
2z-1=-9+24z-36
22z=44
z=2




2009-12-07T23:27:07+01:00
B)
2(x² - 6x + 9) - (x - 7) = 14 - 2(1 - x²)
2x² - 12x + 18 - x + 7 = 14 - 2 + 2x²
- 13x = 12 - 25
- 13x = - 13 |:(-13)
x = 1

c)
3(y² - 2y + 1) - (y + 4) - 12 = 3(y² - 16)
3y² - 6y + 3 - y - 4 - 12 = 3y² - 48
- 6y + 3 - y - 16 = - 48
- 7y = - 48 + 13
- 7y = - 35 |:(-7)
y = 5

d)
9y² - 12y + 4 - 4(y² + 2y + 1) = 5(y² - 1) - 1
9y² - 12y + 4 - 4y² - 8y - 4 = 5y² - 5 -1
- 20y = - 6 |:(-20)
y = 6/20
y = 0,3

e)
2(z - 0,5) = 4z² - 9 - 4(z² - 6z + 9)
2z - 1 = 4z² - 9 - 4z² + 24z - 36
2z - 24z = - 45 + 1
22z = 44 |:22
z = 2

f)
3(z² - 2z + 1) - 2(z² - 4z + 4) - 12z = 6 - (1 - z²)
3z² - 6z + 3 - 2z² + 8z - 8 - 12z = 6 - 1 + z²
- 10z = 5 + 5
- 10z = 10 |:(-10)
z = - 1

Pierwszy rozwiązujący popełnił mały błąd :)